MENINGKATKAN HASIL BELAJAR LOMPAT JAUH MELALUI PENDEKATAN PERMAINAN LONCAT KATAK PADA SISWA KELAS V SD NEGERI JENGGOT KOTA PEKALONGAN TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
Background issue in this study is the lack of proper learning and inadequate facilities in the long jump thelearning process so that the results are not optimal student learning. Formulation of the problem how toimprove the learning outcomes approach long jump through a leapfrog game in the fifth grade SD NegeriJenggot Pekalongan City in the academic year 2012/2013. This study uses PTK. Subjects in this study werethe fifth grade students of SD Negeri Jenggot Pekalongan. Object of this study is learning to use the long jumpfrog jump game. Collecting data in this study designed two cycles, namely cycle 1 and cycle 2. The resultsshowed that the activity score increased to discipline students increased to 10 in the second cycle. Total activityscore of students in the first cycle and the second cycle 32.20 increased to 45.26. The average score on the firstcycle of 6.44, which includes the unfavorable category and the second cycle increased to 9.05 were categorized asgood. Conclusions This study suggests that improving learning outcomes approach long jump frog jump gamein the fifth grade students of SD Negeri Jenggot Pekalongan City in the Academic Year 2012/2013 includingboth categories.